Detection of antibodies against Rift Valley Fever Virus using a Plaque Reduction Neutralization Test (PRNT) - Smith, MaRyka R.; Ragan, I.K.; Wilson, W.C.; Davis, A.S (My University, 2017)
Rift Valley Fever Virus (RVFV) is an arbovirus endemic to Africa. Infections primarily cause abortions and neonatal death in ruminants such as sheep and cattle. However, it can also cause disease in humans, which can lead to death. In order to understand and monitor the spread of RVFV, accurate and rapid diagnostic tests are needed. In order to determine a new diagnostic test’s sensitivity, its ability to detect small concentrations of viral antigen, and specificity, its ability to correctly identify the desired antigen, it must be compared to the current gold standard diagnostic method. The gold standard for determining RVFV infection in ruminants is an 80% plaque reduction neutralization test (PRNT80). This test is a serological assay that detects the presence of neutralizing antibodies to RVFV in serum. Animals are typically positive by RVFV PRNT80 once they have been infected for 3 to 4 days. Currently, our lab is developing a fluorescence multiplexed bead-based immunoassay (FMIA) for detection of antibodies raised against multiple RVFV proteins as well as validating multiple enzyme-linked immunosorbent assays (ELISA) for RVFV. These tests are faster and easier to conduct than the PRNT80. However, their sensitivity and specificity is unknown. Thus, here we determined the PRNT80 values for a population of serum samples for use with validation of these new diagnostic assays. Samples from sheep and cattle that had been infected with various RVFV strains, vaccinated for RVFV, or had no exposure to RVFV were tested. Serum was considered to be positive for neutralizing antibodies for RVFV when there was an 80% reduction in viral plaque formation. The 80% threshold is based on the statistical logic that 100% neutralization is unreasonable to achieve but 50% neutralization could happen by chance. Furthermore, the antibody titer is the most dilute sample that achieves 80% reduction in viral plaque formation. This value is presented as the inverse of the dilution ratio. The PRNT80 confirmed that the samples infected with RVFV had neutralizing antibodies and those that were not exposed to RVFV had less than 1:10 neutralizing antibodies. Here we present a subset of the serum population on which we conducted the PRNT80.
Keywords: Spring 2017